CARD9 prevents lung cancer development by suppressing the expansion of myeloid‐derived suppressor cells and IDO production. Issue 8 (6th May 2019) - Qu, Junxing; Liu, Ling; Xu, Qianyun; Ren, Jing; Xu, Zhen; Dou, Huan; Shen, Sunan; Hou, Yayi; Mou, Yongbin; Wang, Tingting
Abstract : Caspase recruitment domain‐containing protein 9 (CARD9) is an adaptor protein and highly expressed in myeloid cells. Our previous study demonstrates a critical protective effect of CARD9 in the development of colitis‐associated colon cancer. Nevertheless, the effect of CARD9 in lung cancer remains unclear. Here, using a mouse Lewis lung cancer model, we found the tumor burden of CARD9 −/− mice was much heavier than that in wild‐type (WT) mice. More myeloid‐derived suppressor cells (MDSCs) were accumulated and less cytotoxicity T lymphocyte was found in tumor tissues of CARD9 −/− mice, compared to WT mice. Depleting MDSCs using anti‐Gr1 antibody can significantly decrease tumor burden in CARD9 −/− mice. Furthermore, the noncanonical nuclear factor‐kappaB (NF‐κB) pathway was activated in CARD9 −/− mice‐derived MDSCs. Deficiency of CARD9 enhanced expression of indoleamine 2, 3‐dioxygenase (IDO) in MDSCs via noncanonical NF‐κB pathway. Moreover, correlations between CARD9 expressions and MDSCs relative genes ( IDO, iNOS‐2 and arginase 1 [ ARG‐1 ]) were further confirmed in tumor tissues from lung cancer patients. Taken together, we showed a CARD9‐NF‐κB‐IDO pathway in MDSCs which can inhibit the suppressive function of MDSCs and prevent lung cancer development. Abstract : What's new? Myeloid‐derived suppressor cells (MDSCs) play a critical role in enabling tumor immune escape. Factors capable of counteracting MDSC activity in the tumor microenvironment remain largely unknown. Here, the authors identify caspase recruitment domain‐containing protein 9 (CARD9), a myeloid cell adaptor protein, as an inhibitor of MDSCs and indoleamine 2, 3‐dioxygenase (IDO), an immunosuppressive enzyme produced by MDSCs. In mice, CARD deficiency was associated with increased lung tumor size and impaired immune response. Non‐canonical NF‐kB pathway signaling and IDO expression were enhanced in CARD‐deficient cells. The findings suggest that CARD9 is an important immune regulator in the lung tumor microenvironment.